2017
DOI: 10.1108/ilt-09-2015-0129
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of tribological behavior of plasma- and high-velocity oxygen fuel-sprayed WC-10Co-4Cr coatings

Abstract: Purpose The purpose of this study is to prepare WC-10Co-4Cr coatings using two processes of plasma spraying and high-velocity oxygen fuel (HVOF) spraying. The decarburization behaviors of the different processes are analyzed individually. The microstructural characteristics of the as-sprayed coatings are presented and the wear mechanisms of the different WC–10Co–4Cr coatings are discussed in detail. Design/methodology/approach The WC–10Co–4Cr coatings were formed on the surface of Q235 steel by plasma and HV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Thermally sprayed tungsten carbide/cobalt (WC-Co) coatings have many practical applications in the field of aviation, automobile, mechanical power, energy, papermaking and so on (Mohanty and Roy, 2012; Cui et al , 2017). WC-Co coatings can be prepared by various thermal spraying techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Thermally sprayed tungsten carbide/cobalt (WC-Co) coatings have many practical applications in the field of aviation, automobile, mechanical power, energy, papermaking and so on (Mohanty and Roy, 2012; Cui et al , 2017). WC-Co coatings can be prepared by various thermal spraying techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the low content of N and C atoms in the wear area is that EDS analysis of N and C elements with lighter atomic mass is only qualitative analysis (Xue et al , 2021). In the comprehensive results, it was found that the wear mechanism of carbide coating on TA15 substrates is abrasive wear and oxidation wear (Cui et al , 2017). S1 and S3 samples have clearly been worn through at 300°C [Figure 5(d)–(f)].…”
Section: Resultsmentioning
confidence: 99%
“…From the above discussion, it can be noticed that the use of Nickel is suggested by several researchers for erosion and corrosion slurry environment. Researchers (Berger, 2015; Cui et al , 2017; Vencl, Mrdak and Hvizdos, 2017; Kumar et al , 2018b; Singh et al , 2019) reported that the Ni, WC, Co and Ti elements are the popular choice as coating materials which can be deposited by varying the blending with other powders to obtain the alloy or composite coatings.…”
Section: Introductionmentioning
confidence: 99%